Are women included in the private turn? : a case study on how women's empowerment is taken into account in Finnfund's investments to the global south - Seppänen, Jenni (2019)
The overall aim of the research was to study how women and women’s empowerment are included in private finance for development. During recent years, the importance of private finance for development has increased while public finance in many countries has decreased. This phenomenon, the private turn in development finance, has been present in development policies worldwide.